День из жизни писателя: литературный обзор / Г. Г. Степанов - Степанов Георгий Георгиевич (Современная Россия, 1987)
Экземпляры: (20170406) / Инвентарный номер: 17313 / Цена: 0.75 / Авт.знак: С 79 / ББК: 83.3Р1